Motivation, Organizational Culture, and Organizational Commitment on Job Satisfaction and Teacher Performance at State Junior High School, Bangko Rokan Hilir, Riau - Kersiati; Wijaya, Evelyn; Sudarno (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
This study aims to analyze the effect of motivation, organizational culture, and commitment on job satisfaction and teacher performance at SMP Negeri BangkoRohil, Riau. This study took a sample of 78 civil servant teachers at SMP Negeri Bangko District, Rohil, Riau. Data were collected by using a questionnaire or questionnaire and then statistically analyzed using smart PLS. The results of the hypothesis test state that work motivation have a positive and significant effect on job satisfaction but is not significant positive on teacher performance, organizational culture has a positive and significant effect on job satisfaction but is negative and not significant on teacher performance, organizational commitment has a positive and insignificant effect on teacher performance. But job satisfaction is negative and not significant on teacher performance, then job satisfaction has a positive and significant effect on teacher performance at SMP Negeri Bangko, Rohil District.